Bullying Prevention Strategy Through The Role of Education Center - Milenia Vebriyanti, Mega; Suherman, Irman; Herlina, Lina (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze bullying prevention strategies through the role of the Tripusat Pendidikan (Education Tricenter) which includes the government, schools, and the community. The phenomenon of bullying in the current educational environment shows increasingly complex forms, including physical, verbal, social violence, and cyberbullying, which have serious impacts on the psychological condition and development of students. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that the government plays a role in formulating policies and regulations, schools play a role in implementing character education and counseling services, while the community and parents play a role in character formation and child supervision. However, implementation in the field still faces obstacles in the form of less than optimal synergy between parties. Therefore, a collaborative strategy based on the Tripusat Pendidikan is an important approach in creating a safe, inclusive, and bullying-free educational environment.